Hadith #4331 - Sunan al-Nasa'i - Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Ishaq bin Ibrahim bin Muhammad إسحاق بن إبراهيم بن محمد; Khalid bin al-Walid; Thaur bin Yazid al-Rahbi ثور بن يزيد (Sunan al-Nasa'i)
“A man brought a mastigure to the Messenger of Allah and he started looking at it, and turning it over. He said: ‘A nation was transformed, it is not known what they did, and I do not know if this is one of them.”
Grade:

Hadith #4332 - Sunan al-Nasa'i - Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Kathir bin 'Ubaid bin Nmyr كثير بن عبيد بن نمير المذحجي; Khalid bin al-Walid; Thaur bin Yazid al-Rahbi ثور بن يزيد (Sunan al-Nasa'i)
a man brought a mastigure to the Prophet and he said? “A nation was transformed, and Allah knows best “
Grade:

Hadith #4528 - Sunan al-Nasa'i - Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Thaur bin Yazid al-Rahbi ثور بن يزيد; Yahya bin Hamza bin Waqd يحيى بن حمزة بن واقد (Sunan al-Nasa'i)
“The Messenger of Allah forbade Gharar transaction and Hasah transactions.”
Grade:

Hadith #2192 - Sunan Abi Dawud - Ibn Ishaq محمد بن إسحاق بن يسار‎; Ibrahim bin Sa'd bin Ibrahim إبراهيم بن سعد بن إبراهيم; Muhammad bin 'Ubaid al-Tanafasi محمد بن عبيد بن أبي أمية الطنافسي; Thaur bin Yazid al-Rahbi ثور بن يزيد; Ubaidullah bin Sa'd bin Ibrahim b. Sa'd عبيد الله بن سعد بن إبراهيم بن سعد; Ya'qub bin Ibrahim bin Sa'd يعقوب بن إبراهيم بن سعد بن إبراهيم (Sunan Abi Dawud)
The above tradition has also been transmitted by ‘Amr bin Shu’aib through a different chain of narrators. This version adds The Prophet (ﷺ) said “There is no vow except in an act which seeks the pleasure of Allah, the Exalted.
Grade: Hasan

Hadith #2420 - Sunan Abi Dawud - al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك; Khalid bin Ma'dan خالد بن معدان; Sufyan bin Habib al-Basri سفيان بن حبيب البصري; Thaur bin Yazid al-Rahbi ثور بن يزيد (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) as saying: None of you must fast on Friday unless he fasts the day before or the day after.
Grade: Sahih

Hadith #2541 - Sunan Abi Dawud - al-Dahhak bin Mukhlad Abu 'Asim al-Nabil الضحاك بن مخلد أبو عاصم النبيل; al-Hythm bin Hameed al-Ghsany الهيثم بن حميد الغساني مولاهم أبو أحمد; al-Rabi' bin Nafi' Abu Tawba al-Halbi الربيع بن نافع أبو توبة الحلبي; Khshysh bin Asrm bin al-'Aswad خشيش بن أصرم بن الأسود; Thaur bin Yazid al-Rahbi ثور بن يزيد; Utba bin Abd al-Slmy (Sunan Abi Dawud)
The Messenger of Allah (ﷺ) said: If anyone fights in Allah’s path as long as the time between two milkings of a she-camel, Paradise will be assured for him. If anyone sincerely asks Allah for being killed and then dies or is killed, there will be a reward of a martyr for him. Ibn al-Musaffa added from here: If anyone is wounded in Allah’s path, or suffers a misfortune, it will come on the Day of resurrection as copious as possible, its colour saffron, and its odour musk; and if anyone suff
Grade: Sahih

Hadith #3789 - Sunan Abi Dawud - Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Haywat bin Sharih bin Safwan حيوة بن شريح بن صفوان التجيبي; Khalid bin al-Walid; Thaur bin Yazid al-Rahbi ثور بن يزيد (Sunan Abi Dawud)
On the day of Khaybar we slaughtered horses, mules, and assess. The Messenger of Allah (ﷺ) forbade us (to eat) mules and asses, but he did not forbid horse-flesh.
Grade: Sahih

Hadith #4605 - Sunan Abi Dawud - Abdur Rahman bin 'Amr bin 'Absa عبد الرحمن بن عمرو بن عبسة; Ahmad bin Hanbal أحمد بن حنبل; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Khalid bin Ma'dan خالد بن معدان; Thaur bin Yazid al-Rahbi ثور بن يزيد (Sunan Abi Dawud)
The Prophet (ﷺ) said: Let me not find one of you reclining on his couch when he hears something regarding me which I have commanded or forbidden and saying: We do not know. What we found in Allah’s Book we have followed.
Grade: Sahih

Hadith #97 - Jami' al-Tirmidhi - al-Mughira ibn Shu'ba; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Rja'a bin Hywh رجاء بن حيوة; Thaur bin Yazid al-Rahbi ثور بن يزيد (Jami' al-Tirmidhi)
“The Prophet wiped over the Khuff and its bottom.”
Grade:

Hadith #744 - Jami' al-Tirmidhi - Abdullah bin Basr al-Maazni; Hameed bin Musa'da bin al-Mubarak حميد بن مسعدة بن المبارك; Khalid bin Ma'dan خالد بن معدان; Sufyan bin Habib al-Basri سفيان بن حبيب البصري; Thaur bin Yazid al-Rahbi ثور بن يزيد (Jami' al-Tirmidhi)
the Messenger of Allah said: “Do not fast on Saturday except for what has been made obligatory upon you (by Allah). If one of you does not find but a grape peal or a tree’s twig, then let him chew it.”
Grade:

Hadith #745 - Jami' al-Tirmidhi - Abdullah bin Da'ud al-Kharaybi عبد الله بن داود أبو عبد الرحمن الخريبي; Aisha bint Abi Bakr; Amr bin Abi Salmah عمرو بن أبي سلمة التنيسي; Khalid bin Ma'dan خالد بن معدان; Rabi'yah al-Jrshy ربيعة الجرشي; Thaur bin Yazid al-Rahbi ثور بن يزيد (Jami' al-Tirmidhi)
“The Prophet used to try to fast on Mondays and Thursdays.”
Grade:

Hadith #2322 - Jami' al-Tirmidhi - Habib bin 'Ubaid al-Rhby حبيب بن عبيد الرحبي; Muhammad bin Bashar Bindar محمد بن بشار بندار; Thaur bin Yazid al-Rahbi ثور بن يزيد; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Jami' al-Tirmidhi)
I heard Mustawrid, a member of Banu Fihr, saying: The Messenger of Allah (s.a.w) said: “The world compared to the Hereafter is but like what one of you gets when placing his finger into the sea, so look at what you draw from it.”
Grade:

Hadith #2622 - Jami' al-Tirmidhi - Ahmed bin Manay' أحمد بن منيع; Khalid bin Ma'dan خالد بن معدان; Mu'adh ibn Jabal; Muhammad bin al-Hasan bin Abi Yazid محمد بن الحسن بن أبي يزيد الهمداني; Thaur bin Yazid al-Rahbi ثور بن يزيد (Jami' al-Tirmidhi)
that he heard the Messenger of Allah (ﷺ) say: “Whoever is pleased with Allah as (his) Lord, and Islam as (his) religion, and Muhammad as (his) Prophet, then he has tasted the sweetness of faith.”
Grade:

Hadith #2905 - Jami' al-Tirmidhi - Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Thaur bin Yazid al-Rahbi ثور بن يزيد; Waki' bin al-Jarrah وكيع بن الجراح (Jami' al-Tirmidhi)
“I passed by the Masjid when the people were absorbed in story-telling. So I entered upon ‘Ali and said: ‘O Commander of the believers! Do you not see the people are becoming engrossed in story-telling?’ He said: ‘They have been consumed with it?’ I said: “Yes.’ He said: ‘As for me, I heard the Messenger of Allah (ﷺ) saying: “Indeed there comes a Fitnah” So I said: “What is the way out from it O Messenger of Allah?” He said: “Allah’s book. In it is news for what h
Grade:

Hadith #46 - Sunan Ibn Majah - Arbad bin Sariyya al-Salmi; Khalid bin Ma'dan خالد بن معدان; Thaur bin Yazid al-Rahbi ثور بن يزيد; Yahya bin Hakeem al-Maquuam يحيى بن حكيم المقوم (Sunan Ibn Majah)
“The Messenger of Allah said: ‘When anyone of you cleans himself, he should not clean himself with his right hand. Let him clean himself with his left hand.'”
Grade:

Hadith #361 - Sunan Ibn Majah - Abdul Malik bin al-Sbah al-Msm'y عبد الملك بن الصباح المسمعي; Abu Hurairah; Muhammad bin Bashar Bindar محمد بن بشار بندار; Thaur bin Yazid al-Rahbi ثور بن يزيد (Sunan Ibn Majah)
She experienced prolonged non-menstrual bleeding during the time of the Messenger of Allah. She came to the Messenger of Allah and said: “I am suffering prolonged and painful bleeding.” He said: “Fill it with a pad of cloth.” She said: “It is worse than that, it is flowing copiously.” He said: “Then bind yourself with a cloth and observe your menses for six or seven days, in the knowledge of Allah, then have a bath and perform prayer and fast for twenty-three or twenty-four days. D
Grade:

Hadith #593 - Sunan Ibn Majah - al-Mughira ibn Shu'ba; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Rja'a bin Hywh رجاء بن حيوة; Thaur bin Yazid al-Rahbi ثور بن يزيد (Sunan Ibn Majah)
It was narrated that Malik bin Huwairith said that when the Messenger of Allah (ﷺ) said Allahu Akbar, he would raise his hands until they were close to his ears; when he bowed in Ruku’ he did likewise, and when he raised his head from Ruku’ he did likewise.
Grade:

Hadith #1472 - Sunan Ibn Majah - Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Isma'il bin 'Abdullah, al-Sakri إسماعيل بن عبد الله بن خالد - السكري; Thaur bin Yazid al-Rahbi ثور بن يزيد; Ziyad bin Abi Swd'h زياد بن أبي سودة (Sunan Ibn Majah)
“Fasting the day of ‘Ashura’, I hope, will expiate for the sins of the previous year.”
Grade:

Hadith #1718 - Sunan Ibn Majah - Aisha bint Abi Bakr; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Khalid bin Ma'dan خالد بن معدان; Thaur bin Yazid al-Rahbi ثور بن يزيد; Yahya bin Hamza bin Waqd يحيى بن حمزة بن واقد (Sunan Ibn Majah)
“The Messenger of Allah never beat any of his servants, or wives, and his hand never hit anything.”
Grade:

Hadith #1797 - Sunan Ibn Majah - Abdullah bin Basr al-Maazni; Abu Bakr bin Abi Shayba أبو بكر بن أبي شيبة; Isa bin Yonus bin Abi Ishaq عيسى بن يونس بن أبي إسحاق; Khalid bin Ma'dan خالد بن معدان; Thaur bin Yazid al-Rahbi ثور بن يزيد (Sunan Ibn Majah)
“Blessed is the One Whose hearing encompasses all things. I heard some of the words of Khawlah bint Tha’labah, but some of her words were not clear to me, when she complained to the Messenger of Allah (ﷺ) about her husband, and said: ‘O Messenger of Allah, (ﷺ) he has consumed my youth and I split my belly for him (i.e., bore him many children), but when I grew old and could no longer bear children he declared Zihar upon me; O Allah, I complain to You.’ She continued to complain until
Grade:

Hadith #1811 - Sunan Ibn Majah - Aisha bint Abi Bakr; Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Khalid bin Ma'dan خالد بن معدان; Thaur bin Yazid al-Rahbi ثور بن يزيد; Yahya bin Hamza bin Waqd يحيى بن حمزة بن واقد (Sunan Ibn Majah)
“Barirah was told to observe the waiting period for three menstrual cycles.”
Grade:

Hadith #1854 - Sunan Ibn Majah - Abu Umama bin Sahl; Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Khalid bin Ma'dan خالد بن معدان; Thaur bin Yazid al-Rahbi ثور بن يزيد (Sunan Ibn Majah)
“The oath is only according to the intention of the one who requests the oath to be taken.”‘
Grade:

Hadith #2242 - Sunan Ibn Majah - Khalid bin Ma'dan خالد بن معدان; Sahl bin Znjlh سهل بن زنجلة; Thaur bin Yazid al-Rahbi ثور بن يزيد; Ubayy ibn Ka'b; Yahya bin Sa'id bin Farroukh al-Qatan يحيى بن سعيد بن فروخ القطان (Sunan Ibn Majah)
“I went out with Zaid bin Suhan and Salman bin Rabi’ah, and when we were at `Udhaib, I found a whip. They said to me: ‘Throw it away,’ but I refused. When we came to Al-Madinah I went to Ubayy bin Ka’b and told him about that. He said: ‘You did the right thing. I found one hundred dinar that had been lost at the time of the Messenger of Allah (ﷺ), and I asked him about it. He said, “Announce it for a year.” So I Announced it, and I did not find anyone who recognized it. He said
Grade:

Hadith #2304 - Sunan Ibn Majah - Hisham bin 'Ammar bin Nasayr هشام بن عمار بن نصير; Ibn Jurayj ابن جريج; Jabir ibn 'Abdullah; Muhammad bin Muslim bin Tadras محمد بن مسلم بن تدرس أبو الزبير; Thaur bin Yazid al-Rahbi ثور بن يزيد; Yahya bin Hamza bin Waqd يحيى بن حمزة بن واقد (Sunan Ibn Majah)
“If one man says another: ‘O effeminate one!’ give him twenty lashes. And if one man says to another: ‘O homosexual!’ give him twenty twenty lashes.”
Grade:

Hadith #3317 - Sunan Ibn Majah - Baqiyya bin al-Walid bin Sa'aid بقية بن الوليد بن صائد; Khalid bin al-Walid; Thaur bin Yazid al-Rahbi ثور بن يزيد (Sunan Ibn Majah)
“A hand span.” ‘Aishah said: “This may show her calves.” He said: “Then a forearm’s length.”
Grade:

Hadith #3407 - Sunan Ibn Majah - Abdur Rahman bin Ibrahim عبد الرحمن بن إبراهيم - دحيم; Abu Umama al-Bahili; al-Walid bin Muslim al-Quraishi الوليد بن مسلم القرشي; Khalid bin Ma'dan خالد بن معدان; Thaur bin Yazid al-Rahbi ثور بن يزيد (Sunan Ibn Majah)
“Jibra’il kept enjoining good treatment of neighbours untol I thought that he would make neigbours heirs.”
Grade:

Hadith #3507 - Sunan Ibn Majah - Abd al-Salam bin Abd عبد السلام بن عبد القدوس بن حبيب; Abu Umama al-Bahili; Khalid bin Ma'dan خالد بن معدان; Thaur bin Yazid al-Rahbi ثور بن يزيد (Sunan Ibn Majah)
“Whenever the Messenger of Allah(ﷺ) came back from a journey, he would be met by us(children). (One day) he was met by me and Hasan or Husain. He made one of us ride in front of him and the other behind him, until we came to Al-Madinah.”
Grade:

Hadith #3625 - Sunan Ibn Majah - Abdul Malik bin al-Sbah al-Msm'y عبد الملك بن الصباح المسمعي; Abu Hurairah; Thaur bin Yazid al-Rahbi ثور بن يزيد (Sunan Ibn Majah)
“If the Messenger of Allah (ﷺ) saw a cloud that looked as if it was bringing rain, the color of his face would change, and he would go in and out and walk to and fro. Then, if it rained, he would feel relieved.” ‘Aishah mentioned to him what she had seen him do, and he said: “How do you know? Perhaps it would be as the people of Hud said: ‘Then, when they saw it as a dense cloud coming towards their valleys, they said: “This is a cloud bringing us rain!” Nay, but it is that (torm
Grade: